Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In order to find $f(x)$ so that $F(u)=\sum\limits_{x=0}^\infty f(x)\sin\dfrac{\pi ux}{L}$ and $F(u)=\sum\limits_{x=0}^\infty f(x)\cos\dfrac{\pi ux}{L}$ , we can borrow the idea from Fourier sine series and Fourier cosine series so that the results are $f(x)=\dfrac{2}{L}\int_0^LF(u)\sin\dfrac{\pi xu}{L}du$ and $f(x)=\begin{cases}\dfrac{1}{L}\int_0^LF(u)~du&\text{when}~x=0\\\dfrac{2}{L}\int_0^LF(u)\cos\dfrac{\pi xu}{L}du&\text{when}~x\neq0\end{cases}$ respectively, but unfortunately the above formulae only hold for $u\in(0,L)$ .

So do they exist any better formula of $f(x)$ so that really hold for at least $u\in\mathbb R$ ?

But why the continuous versions $F(u)=\int_0^\infty f(x)\sin ux~dx$ and $F(u)=\int_0^\infty f(x)\cos ux~dx$ can exist formulae $f(x)=\dfrac{2}{\pi}\int_0^\infty F(u)\sin xu~du$ and $f(x)=\dfrac{2}{\pi}\int_0^\infty F(u)\cos xu~du$ respectively so that they really hold for at least $u\in\mathbb R$ ?

share|improve this question
    
I think Fourier transform is an answer to your first question. Just split the real and imaginary parts. (I actually don't quite understand the question.) –  Tunococ Aug 17 '12 at 2:53
add comment

1 Answer

up vote 0 down vote accepted

In fact we can slightly modify the derivations in Fourier sine series and Fourier cosine series to get the formulae of $f(x)$ which hold for $u\in\mathbb R$ :

Part $1$ :

$F(u)=\sum\limits_{x=0}^\infty f(x)\sin\dfrac{\pi ux}{L}$

$F(u)\sin\dfrac{\pi yu}{L}=\sum\limits_{x=1}^\infty f(x)\sin\dfrac{\pi xu}{L}\sin\dfrac{\pi yu}{L}$

$\int_{kL}^{(k+1)L}F(u)\sin\dfrac{\pi yu}{L}du=\int_{kL}^{(k+1)L}\sum\limits_{x=1}^\infty f(x)\sin\dfrac{\pi xu}{L}\sin\dfrac{\pi yu}{L}du$ , $\forall k\in\mathbb{Z}$

$\int_{kL}^{(k+1)L}F(u)\sin\dfrac{\pi yu}{L}du=\sum\limits_{x=1}^\infty f(x)\int_{kL}^{(k+1)L}\sin\dfrac{\pi xu}{L}\sin\dfrac{\pi yu}{L}du$ , $\forall k\in\mathbb{Z}$

$\because\int_{kL}^{(k+1)L}\sin\dfrac{\pi xu}{L}\sin\dfrac{\pi yu}{L}du$

$=\int_{kL}^{(k+1)L}\dfrac{1}{2}\biggl(\cos\dfrac{\pi(x-y)u}{L}-\cos\dfrac{\pi(x+y)u}{L}\biggr)du$

$=\begin{cases}\biggl[\dfrac{L}{2\pi(x-y)}\sin\dfrac{\pi(x-y)u}{L}-\dfrac{L}{2\pi(x+y)}\sin\dfrac{\pi(x+y)u}{L}\biggr]_{kL}^{(k+1)L}&\text{when}~x\neq y~\text{and}~x\neq-y\\\biggl[\dfrac{u}{2}-\dfrac{L}{2\pi(x+y)}\sin\dfrac{\pi(x+y)u}{L}\biggr]_{kL}^{(k+1)L}&\text{when}~x=y\\\biggl[\dfrac{L}{2\pi(x-y)}\sin\dfrac{\pi(x-y)u}{L}-\dfrac{u}{2}\biggr]_{kL}^{(k+1)L}&\text{when}~x=-y\\\left[0\right]_{kL}^{(k+1)L}&\text{when}~x=y~\text{and}~x=-y\end{cases}$

$=\begin{cases}0&\text{when}~x,y~\text{and}~k~\text{are integers and}~x\neq y~\text{and}~x\neq-y~\text{and}~(x=y~\text{and}~x=-y)\\\dfrac{L}{2}&\text{when}~x,y~\text{and}~k~\text{are integers and}~x=y\\-\dfrac{L}{2}&\text{when}~x,y~\text{and}~k~\text{are integers and}~x=-y\end{cases}$

$\therefore\int_{kL}^{(k+1)L}F(u)\sin\dfrac{\pi yu}{L}du=f(y)\dfrac{L}{2}$ , $\forall k\in\mathbb{Z}$ , $u\in(kL,(k+1)L)$

$f(y)=\dfrac{2}{L}\int_{kL}^{(k+1)L}F(u)\sin\dfrac{\pi yu}{L}du$ , $\forall k\in\mathbb{Z}$ , $u\in(kL,(k+1)L)$

$f(x)=\dfrac{2}{L}\int_{kL}^{(k+1)L}F(u)\sin\dfrac{\pi xu}{L}du$ , $\forall k\in\mathbb{Z}$ , $u\in(kL,(k+1)L)$

Hence $f(x)=\sum\limits_{k=-\infty}^\infty\dfrac{2\prod_{kL,(k+1)L}(u)}{L}\int_{kL}^{(k+1)L}F(u)\sin\dfrac{\pi xu}{L}du$ , $\forall k\in\mathbb{Z}$ , $u\in\mathbb R$

Part $2$ :

$F(u)=\sum\limits_{x=0}^\infty f(x)\cos\dfrac{\pi ux}{L}$

$F(u)\cos\dfrac{\pi yu}{L}=\sum\limits_{x=0}^\infty f(x)\cos\dfrac{\pi xu}{L}\cos\dfrac{\pi yu}{L}$

$\int_{kL}^{(k+1)L}F(u)\cos\dfrac{\pi yu}{L}du=\int_{kL}^{(k+1)L}\sum\limits_{x=0}^\infty f(x)\cos\dfrac{\pi xu}{L}\cos\dfrac{\pi yu}{L}du$ , $\forall k\in\mathbb{Z}$

$\int_{kL}^{(k+1)L}F(u)\cos\dfrac{\pi yu}{L}du=\sum\limits_{x=0}^\infty f(x)\int_{kL}^{(k+1)L}\cos\dfrac{\pi xu}{L}\cos\dfrac{\pi yu}{L}du$ , $\forall k\in\mathbb{Z}$

$\because\int_{kL}^{(k+1)L}\cos\dfrac{\pi xu}{L}\cos\dfrac{\pi yu}{L}du$

$=\int_{kL}^{(k+1)L}\dfrac{1}{2}\biggl(\cos\dfrac{\pi(x-y)u}{L}+\cos\dfrac{\pi(x+y)u}{L}\biggr)du$

$=\begin{cases}\biggl[\dfrac{L}{2\pi(x-y)}\sin\dfrac{\pi(x-y)u}{L}+\dfrac{L}{2\pi(x+y)}\sin\dfrac{\pi(x+y)u}{L}\biggr]_{kL}^{(k+1)L}&\text{when}~x\neq y~\text{and}~x\neq-y\\\biggl[\dfrac{u}{2}+\dfrac{L}{2\pi(x+y)}\sin\dfrac{\pi(x+y)u}{L}\biggr]_{kL}^{(k+1)L}&\text{when}~x=y\\\biggl[\dfrac{L}{2\pi(x-y)}\sin\dfrac{\pi(x-y)u}{L}+\dfrac{u}{2}\biggr]_{kL}^{(k+1)L}&\text{when}~x=-y\\\left[u\right]_{kL}^{(k+1)L}&\text{when}~x=y~\text{and}~x=-y\end{cases}$

$=\begin{cases}0&\text{when}~x,y~\text{and}~k~\text{are integers and}~x\neq y~\text{and}~x\neq-y\\\dfrac{L}{2}&\text{when}~x,y~\text{and}~k~\text{are integers and}~x=y\\\dfrac{L}{2}&\text{when}~x,y~\text{and}~k~\text{are integers and}~x=-y\\L&\text{when}~x,y~\text{and}~k~\text{are integers and}~x=y~\text{and}~x=-y\end{cases}$

$\therefore\begin{cases}\int_{kL}^{(k+1)L}F(u)~du=f(0)L\\\int_{kL}^{(k+1)L}F(u)\cos\dfrac{\pi yu}{L}du=f(y)\dfrac{L}{2}&\text{when}~y\neq0\end{cases}$ , $\forall k\in\mathbb{Z}$ , $u\in(kL,(k+1)L)$

$f(y)=\begin{cases}\dfrac{1}{L}\int_{kL}^{(k+1)L}F(u)~du&\text{when}~y=0\\\dfrac{2}{L}\int_{kL}^{(k+1)L}F(u)\cos\dfrac{\pi yu}{L}du&\text{when}~y\neq0\end{cases}$ , $\forall k\in\mathbb{Z}$ , $u\in(kL,(k+1)L)$

$f(x)=\begin{cases}\dfrac{1}{L}\int_{kL}^{(k+1)L}F(u)~du&\text{when}~x=0\\\dfrac{2}{L}\int_{kL}^{(k+1)L}F(u)\cos\dfrac{\pi xu}{L}du&\text{when}~x\neq0\end{cases}$ , $\forall k\in\mathbb{Z}$ , $u\in(kL,(k+1)L)$

Hence $f(x)=\begin{cases}\sum\limits_{k=-\infty}^\infty\dfrac{\prod_{kL,(k+1)L}(u)}{L}\int_{kL}^{(k+1)L}F(u)~du&\text{when}~x=0\\\sum\limits_{k=-\infty}^\infty\dfrac{2\prod_{kL,(k+1)L}(u)}{L}\int_{kL}^{(k+1)L}F(u)\cos\dfrac{\pi xu}{L}du&\text{when}~x\neq0\end{cases}$ , $\forall k\in\mathbb{Z}$ , $u\in\mathbb R$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.